AN ANALYSIS OF FLOUTING MAXIMS IN TONI MORRISONâ€™S â€œBELOVEDâ€ (1987) - Dewi, Citra; Putra, Dhanu Ario (JURNAL LITERARY CRITICISM, 2014)
This thesis studies about flouting maxims in Toni Morrison?s ?Beloved?. This study concerns on finding the flouting maxims in the novel and try to find the implicatures that caused by flouting the maxims. By using the descriptive qualitative method, the researcher tried to observe by using critical analyzing way for each conversation that occured in the novel. Each conversation in the novel is observing by considering if it is one kind of conversation that flouting the maxim of quality,quantity,relation or manner which are according to Grice theory about maxims. The setting of conversation in the novel is also take a part as the evidence if it is flouting maxims. Implicatures that caused by the speaker is also become one important element in order to check the effect of flouting maxim. It indicates that in Toni Morrison?s ?Beloved?, occured flouting maxims, all of four maxims had been found in the conversation between the characters. Keywords :conversation, maxim, flouting maxims, characteristics